2022
DOI: 10.1093/genetics/iyac098
|View full text |Cite
|
Sign up to set email alerts
|

Altering enhancer–promoter linear distance impacts promoter competition in cis and in trans

Abstract: In Drosophila, pairing of maternal and paternal homologs can permit trans-interactions between enhancers on one homolog and promoters on another, an example of a phenomenon called transvection. When chromosomes are paired, promoters in cis and in trans to an enhancer can compete for the enhancer’s activity, but the parameters that govern this competition are as yet poorly understood. To assess how the linear spacing between an enhancer and promoter can influence promoter competition in Drosophila, we employed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 101 publications
0
8
0
Order By: Relevance
“…Our results also showed that interactions between Su(Hw) binding sites can support functional trans interactions between enhancers and promoters located on homologous chromosomes and separated by a distance of 28 kb. A well-described phenomenon in Drosophila, called transvection, concerns the ability of an enhancer or silencer located on one of the homologous chromosomes to activate or repress a promoter located on the second homologous chromosome [79][80][81][82]. Using transgenic systems, it has been shown that transvection occurs at most genomic sites [83][84][85].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results also showed that interactions between Su(Hw) binding sites can support functional trans interactions between enhancers and promoters located on homologous chromosomes and separated by a distance of 28 kb. A well-described phenomenon in Drosophila, called transvection, concerns the ability of an enhancer or silencer located on one of the homologous chromosomes to activate or repress a promoter located on the second homologous chromosome [79][80][81][82]. Using transgenic systems, it has been shown that transvection occurs at most genomic sites [83][84][85].…”
Section: Discussionmentioning
confidence: 99%
“…Using transgenic systems, it has been shown that transvection occurs at most genomic sites [83][84][85]. A promoter located in close proximity to an enhancer can block its ability to trans stimulate another promoter located on a homologous chromosome and, thus, suppress transvection [82,86]. The efficiency of transvection between the enhancer and the promoter also generally decreases with increasing distance between their genomic positions and is highly dependent on the sites of integration of the constructs (position effect) [87].…”
Section: Discussionmentioning
confidence: 99%
“…Distance also plays a more pronounced role in regulating the activity of weaker enhancers, as a reporter assay testing the effect of distance on enhancer activity found that the activity of the Nanog enhancer rapidly dropped off as it was shifted from 25kb away from the target gene to 75kb (Henry Thomas et al, 2023). In Drosophila , shifting the GMR enhancer from a few hundred base pairs away to 3kb away completely attenuated its ability to activate a target hsp70 promoter (Bateman & Johnson, 2022). Our study reveals the distance dependent insulation of the Lefty1 gene from the stronger Lefty2 enhancer which may have been involved in the functional divergence of these gene paralogs by allowing for downregulated Lefty1 dosage after the duplication event.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that, by being close to boundaries, developmental genes are more likely to be located at shorter linear distances from their cognate enhancers than the potential competing genes located at the other side of the boundaries. Considering that short linear distances facilitate the functional communication between genes and enhancers 55,56,70 , this might give developmental genes a competitive advantage over genes located on the other side of the "developmental" boundary 71 . At the molecular level, it is currently unclear which mechanisms might explain how active genes contribute to insulation through promoter competition.…”
Section: Discussionmentioning
confidence: 99%